Emerging Artificial Intelligence In Therapeutic Agreements With A Medicolegal Approach - Dewantara, Reka; Pandansari, Rekyan (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Medical services use artificial intelligence for operating to help and even transform the healthcare system. AI innovators have developed tools to improve clinical care processes, advance medical research, and increase efficiency in medical services.Purposes of the Research: The purpose of this article is to analyse the legal validity of therapeutic agreements using AI in medical field.Methods of the Research: The research method used is a normative juridical research type with an analytical approach.Results of the Research: The results show that medical services are complex and closely related systems, and always contain risks, so they must be carried out with great care. Legal provisions governing the use of AI in therapeutic agreements with a medicolegal approach must be able to evaluate and ensure the safety and accuracy of medical decisions made by AI